Processo de reconhecimento não supervisionado de áreas de estacionamento - Mexas, Antonio Henrique (2014)
The detection of objects in an image is important for decision making in a remote sensing system. The interest areas in this kind of work are buildings, streets, bridges, airports, ports and parking. The latter will be addressed in this work. The detection of these objects using manual techniques can be laborious and result in detection errors. This paper examines algorithms to the identification and recognition of parking areas paved and marked. To define the processing the best parameters are analised, with the purpose to obtain more accurate results. This work proposes an algorithm composed of recognition of parking areas that uses important variables such as vehicle size, size of parking spaces, image resolution and camera zoom. The experimental results obtained with the proposed method have a higher hit rate than other academic approaches.